Can teacher education in Australia meet the challenges of the new millennium? - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)

(untitled)
This paper provides a brief discussion of teacher education in Australia, as it faces significant challenges in preparing teachers to take on the academic, technological and emotional demands of teaching as a career.